Development and the Interaction of Enforcement Institutions - Dhillon, Amrita; Rigolini, Jamele (World Bank, Washington, DC, 2012)
The authors examine how institutions that enforce contracts between two parties-producers and consumers-interact in a competitive market with one-sided asymmetric information and productivity shocks. They compare an informal enforcement mechanism, reputation, the efficacy of which is enhanced by consumers investing in "connectedness," with a formal mechanism, legal enforcement, the effectiveness of which can be reduced by producers by means of bribes. When legal enforcement is poor, consumers connect more with one another to improve informal enforcement. In contrast, a well-connected network of consumers reduces producers' incentives to bribe. In equilibrium, the model predicts a positive relationship between the frequency of productivity shocks, bribing, and the use of informal enforcement, providing a physical explanation of why developing countries often fail to have efficient legal systems. Firm-level estimations confirm the partial equilibrium implications of the model.